Crystal structure of poly[(μ 3-3,3″,5,5″-tetrafluoro-(1,1′:4′,1″-terphenyl)-4,4″-dicarboxylate-κ 3 O,O′:O″)-(μ 4-3,3″,5,5″-tetrafluoro-(1,1′:4′,1″-terphenyl)-4,4″-dicarboxylate-κ 4 O,O′,O″,O‴)-dicadmium(II)]dimethylformamide solvate, C47H30Cd2F8N3O12 - Jing Hao; Jing Tang; You-Wen Li; Li-Li Man; Xia Hou; Ke Liu (Zeitschrift für Kristallographie - New Crystal Structures, 2025)
C47H30Cd2F8N3O12, monoclinic, P21/n (no. 14), a = 10.3022(2) Å, b = 53.5533(11) Å, c = 10.4720(2) Å, β = 91.272(2)∘, V = 5776.2(2) Å3, Z = 4, R gt(F) = 0.0983, wR ref (F 2) = 0.2343, T = 100 K.